Students’ Perception of 4Ps Marketing Strategies on Sports Product Purchases in Malaysia - Kutip, Muhammad Faizal; Masukree Kora, Marjan; Mohamad Jaafar, Mohamad Fittrey Hazwann; Mohd Kudzi, Farah Aimi; Samsul, Fareesha Nadhirah (Universitas Majalengka, 2025)
Background: The rapid growth of e-commerce has transformed the retail landscape, especially among younger consumers who increasingly shop online. However, this environment may yield different results compared to traditional brick-and-mortar settings. Purpose: This study aims to investigate the students’ perception of 4Ps Marketing Strategies on Sports Product Purchases in Malaysia. Results: Data analysis using SPSS version 28 revealed significant positive correlations between all four elements of the marketing mix and purchase decisions: place (r = 0.624, p < 0.05), promotion (r = 0.523, p < 0.05), price (r = 0.488, p < 0.05), and product (r = 0.311, p = 0.05). Multiple regression analysis showed a strong correlation between the predictors and purchase decisions, with an R² value of 0.497, explaining 49.7% of the variance. The regression equation predicted purchase decisions as: y = 0.624 + 0.001(product) + 0.311(price) + 0.087(promotion) + 0.428(place). Conclusion: These findings indicate that the online platform's convenience, based on the 4 Ps, significantly impacts students' purchasing decisions. Implications: The study suggests that online retailers should focus on enhancing platform accessibility and user experience while investing in effective promotional and pricing strategies to drive sales and generate revenue in the local market.